Quality of work life among the faculty members of higher education institutions in India / Abirami Arunachalam ... [et al.] - Arunachalam, Abirami; Subbarayalu, Arun Vijay; Ramalingam, Balamourougane; Prabaharan, Sivasankar; Samiappan, Deepa; Marimuthu, Palanivel Rubavathi; Chinnusamy, Sivakumar; Shanmugavelu, Gokila; Neethidoss, Prabu; Ganesan, Balamurugan; Jayaseeli, Nithya (Universiti Teknologi MARA, 2024)
This study adopted an exploratory study design to reveal the quality of work life (QoWL) of the faculty members working at Indian higher education institutions (HEIs), aiming at their gender and various academic specialties in which those are serving. A self-structured QoWL questionnaire was utilised for data collection from the study population, and 547 faculty members responded to the questionnaire used. Based on the findings, 73% of the faculty members at Indian HEIs expressed satisfaction with their QoWL. Faculty members' perceptions of the five QoWL dimensions with regard to their gender and academic specialisations varied significantly (p<0.05). Though, some essential items required the attention of the policymakers of Indian HEIs with the appropriate strategies reinforcing the QoWL, thereby enhancing the faculty members' satisfaction. Such strategies would retain the highly skilled workforce and decline the turnover rate of faculty members in the Indian higher education sector.